Speak to the devil - Duncan, Dave, 1933-2018 (Tor, 2016)
Anton, an ambitious young knight, and Wulfgang, an amiable teenager who hears Voices that may belong to the devil or saints (depending on who tells the tale), join Cardinal Zdenek's forces with the assignment to take the strategic fortress at Cardice, command the army there, and hold Cardice against neighboring enemies.